Cryopreservation of tissues and organs: present, bottlenecks, and future - Chen, Jiangming; Liu, Xiangjian; Hu, Yuying; Chen, Xiaoxiao; Tan, Songwen (Frontiers in Veterinary Science, 2023)
Tissue and organ transplantation continues to be an effective measure for saving the lives of certain critically ill patients. The organ preservation methods that are commonly utilized in clinical practice are presently only capable of achieving short-term storage, which is insufficient for meeting the demand for organ transplantation. Ultra-low temperature storage techniques have garnered significant attention due to their capacity for achieving long-term, high-quality preservation of tissues and organs. However, the experience of cryopreserving cells cannot be readily extrapolated to the cryopreservation of complex tissues and organs, and the latter still confronts numerous challenges in its clinical application. This article summarizes the current research progress in the cryogenic preservation of tissues and organs, discusses the limitations of existing studies and the main obstacles facing the cryopreservation of complex tissues and organs, and finally introduces potential directions for future research efforts.